COMPARATIVE ANALYSIS OF COST AND TIME PLANNING BETWEEN CONVENTIONAL CALCULATION AND BUILDING INFORMATION MODELING (BIM) IN THE OFFICE BUILDING CONSTRUCTION PROJECT OF UPTP BLK PRABUMULIH - Asa, M. Fanshurullah; Alfaritzi, Fadillah (DEARSIP : Journal of Architecture and Civil, 2025)
BIM (Building Information Modeling) is a method in infrastructure construction that integrates virtual models and their technical data and simulates all information on a construction project into 3D, 4D, 5D, 6D, and 7D models. This study aims to model reinforced concrete buildings which are then intended to obtain the volume of work, another objective of this final project is to estimate the cost and time of the work. This study was conducted using a case study on the UPTP BLK Prabumulih Office Building Construction project. The data used in this study were Shop Drawing and RAB data obtained from the relevant contractor, then the data was re-modeled using Tekla Structure software. The results of this study are that the BIM concept can accurately calculate the volume of work and can streamline costs by 6.40% and the work time becomes faster from the initial 115 days to 103 working days.